2019
DOI: 10.29309/tpmj/2019.26.10.1625
|View full text |Cite
|
Sign up to set email alerts
|

Trends of prescribing antibiotics in various dental diseases at different private clinical setups of Sialkot, Pakistan.

Abstract: Objectives: Antibiotics widely used now a day in dental practice for treatment of acute odontogenic, non-odontogenic infections and as a prophylactic purpose for focal infections in patients at possibility for infective endocarditis development as well as prevention of surgical infection of wound and controlling of orofacial infections. Studies of prescribing trends provide information about the quality & pattern of use causes of drug use, and their outcomes. The main objective of this study was to assist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ravichandran et al 17 , Kaul et al 18 and Suhaib et al 19 Agossa et al 20 26 documented that the most commonly prescribed antibiotic was Amoxicillin. However, according to Aly et al 27 Deniz-Sungur et al 28 Javed et al 29 and Shrestha et al 30 , the most often prescribed antibiotic was amoxicillin & clavulanic acid combination. Smith et al 31 found that amoxicillin was among the top antibiotics administered by dentists in England and Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…Ravichandran et al 17 , Kaul et al 18 and Suhaib et al 19 Agossa et al 20 26 documented that the most commonly prescribed antibiotic was Amoxicillin. However, according to Aly et al 27 Deniz-Sungur et al 28 Javed et al 29 and Shrestha et al 30 , the most often prescribed antibiotic was amoxicillin & clavulanic acid combination. Smith et al 31 found that amoxicillin was among the top antibiotics administered by dentists in England and Scotland.…”
Section: Discussionmentioning
confidence: 99%
“…But the overuse and misuse lead to antibiotic resistance, which makes it more difficult for the public health care system to treat people. [10] About 10% of antibiotics are prescribed by dentists [9]. Antibiotic overuse by dentists has been extensively documented in the number of nations [9].…”
Section: Introductionmentioning
confidence: 99%